Developing philosophical discussions with children and young people in residential care homes - Terje Jostein Halvorsen (Scottish Journal of Residential Child Care)
Philosophical discussion in small groups is a method already known in the field of residential child care, through Kohlberg's theory on how to promote young people's ability for moral reasoning. This paper offers a presentation of two philosophers, Matthew Lipman and Gareth Matthews, who advise approaches similar to the Kohlbergian approach but where the aim is to promote cognitive development in multiple domains. Their approaches may prove useful in the endeavours to improve the educational achievements of children and young people in residential care homes. Moreover, these approaches may also promote social competence and social functioning. According to the author, the philosophical knowledge needed to initiate and lead discussions, can yield an additional benefit in the form of a more stringent and in-depth professional reasoning.